Lyapunov-Type Inequalities for Second-Order Boundary Value Problems with a Parameter - Haidong Liu (Discrete Dynamics in Nature and Society)
In this paper, we will establish some new Lyapunov-type inequalities for a class of second-order boundary value problems with a parameter. The inequalities generalize some early results in the literature.